(untitled) (Journal for Studies in Humanities and Social Sciences, 2020)
In Namibia, education is an undisputable right (Ministry of Information and Broadcasting, 1992). The University of Namibia prides itself in being an inclusive education institution and it adheres to national and international legal frameworks advocating inclusivity in higher education. The research that forms the basis of this article emanated from a project of students offering Inclusive Education 1 as a module in teacher education. The research capitalized on a qualitative design in which students took to all spaces (physical, infrastructural, cultural, socio-emotional etc.) of the main campus of the University of Namibia to identify barriers to inclusive education. They were allowed to provide either descriptions (using words) and/or pictures of the barriers they observed. The findings of the study revealed a myriad of exclusive infrastructure and peace threatening spaces. Some of the images that emerged from these activities show a clear disconnect between policies and reality through the students’ “discoveries” of barriers to inclusive education. Hence the recommendation that universities have a responsibility to ensure that equality and equity are achieved and are experienced not only by policy developers and service providers, but also by the beneficiaries of the policies.